SISTEM INFORMASI PELAYANAN UMROH ALKHAIRAT GROUP BERBASIS WEB - Ahmad Aris (Department of Science and Technology Ibrahimy University, 2018)
Registration of Umrah in Jember Alkhairat Group is a regular activity performed almost every month, In implementation Alkhairat ' Umrah during the registration of the Group do not restrict Jember pilgrims to Mecca to perform the applicants, so that the required applications that handle the entire registration process bias ' in order to make it easy for prospective pilgrims to Mecca and it sysop Alkhairat Group registration in the service is doing. This study has formulated the problem how to build information systems services is doing in the web-based Alkhairat Group. Umrah service information system is being developed in the scope of the registration cost of doing ' Umrah and installments only, such as the registration procedures ' in the Alkhairat Group. Research conducted at the information system using the method prototype by using iterative System Development Life in models (SDLC) Cule. Research conducted can be concluded that the information system Services AlKhairat web-based Group can be a tool to assist and facilitate the service of process is doing. Facilities provided in this information system are charging from ' registration ' fee installment, option packages, and reports data umrah applicants with various details.